Relación entre el gasto de salud materno neonatal y la cobertura de los indicadores sanitarios en el distrito de Trujillo 2008-2012 - Florián Plasencia, Ernestina Haydeé (2015)
Neonatal maternal indicators constitute the mainstay of health maternal neonatal therefore get the new being in good health, in all its potentially developed areas with stringent prenatal and post natal; maternal health and budget with leads to great disparities in our country, which translates into little vulnerable inequities. This research had as main purpose to determine what is the relationship between spending and coverage of implementation indicators neonatal maternal health in the District of Trujillo 2008 -2012. . Karena itu memper timbangkan bahwa itu adalah penting penting ini studi doktor yang berjudul hubungan antara pengeluaran kesehatan ibu dan bayi dan cakupan indikator kesehatan di distrik Trujillo 2008-2012. The material was constituted by documents of management follow-up report of financial execution and implementation of physical targets 2008 - 2012. The method used was the hermeneutic inductive method. The results are presented in an input frequency tables with their absolute values, to determine the relationship and correlation analysis of linear regression and coefficient of Pearson correlation and with a significance level of 5% were used. In this way we obtain the final conclusion that there is only 3 positive indicators that are family planning, institutional delivery and control post partum.